Exploring antigenic variation in autoimmune endocrinopathy - Mavridou, Maria; Pearce, Simon H. (Frontiers in Immunology, 2025)
Autoimmune disorders develop owing to a misdirected immune response against self-antigen. Genetic studies have revealed that numerous variants in genes encoding immune system proteins are associated with the development of autoimmunity. Indeed, many of these genetic variants in key immune receptors or transcription factors are common in the pathogenesis of several different autoimmune conditions. In contrast, the proclivity to develop autoimmunity to any specific target organ or tissue is under-researched. This has particular relevance to autoimmune endocrine conditions, where organ-specific involvement is the rule. Genetic polymorphisms in the genes encoding the targets of autoimmune responses have been shown to be associated with predisposition to several autoimmune diseases, including type 1 diabetes, autoimmune thyroid disease and Addison’s disease. Mechanistically, variations leading to decreased intrathymic expression, overexpression, different localisation, alternative splicing or post-translational modifications can interfere in the tolerance induction process. This review will summarise the different ways genetic variations in certain genes encoding endocrine-specific antigens (INS, TSHR, TPO, CYP21A2, PIT-1) may predispose to different autoimmune endocrine conditions.